2004
DOI: 10.1116/1.1824191
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen in Si–Si bond center and platelet-like defect configurations in amorphous hydrogenated silicon

Abstract: Hydrogen and deuterium in bond-centered (BC) and platelet-like configurations were detected in hydrogenated (and deuterated) amorphous silicon thin films deposited from SiH4 and SiD4 plasmas. Infrared absorptions due to these configurations were measured using in situ multiple total internal reflection Fourier transform infrared spectroscopy in a differential mode, where changes in the as-deposited a-Si:H(D) films were observed during D2(H2) plasma exposure. This method coupled with preferential replacement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The process of Hinduced crystallization of a-Si:H by the insertion of H into the strained Si-Si bonds, both on the surface and in the bulk of the film, leads to the formation of (a) a bond-centered hydrogen, where a H atom is present between two Si atoms and is bonded to both Si atoms, (b) an isolated silicon monohydrides where the H atom is bonded to only one Si leaving a DB on the other Si after the break of the strained Si-Si bond, or (c) a Si-Si bond with bond length close to the equilibrium c-Si bond length (2.35 Å ) where the H atom is bonded to only one Si atom after the relaxation of the strained Si-Si bond. 10,39 Silicon hydrides in a platelet-like configuration in which the Si-H bonds are present along a planar defect, i.e., the grain boundaries, are formed just after the passivation of DBs in condition (b) mentioned above by H diffusion. Such a platelet-like configuration is similar to the structures observed in c-Si where Si-H bonds are predominantly oriented along {111} crystallographic planes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of Hinduced crystallization of a-Si:H by the insertion of H into the strained Si-Si bonds, both on the surface and in the bulk of the film, leads to the formation of (a) a bond-centered hydrogen, where a H atom is present between two Si atoms and is bonded to both Si atoms, (b) an isolated silicon monohydrides where the H atom is bonded to only one Si leaving a DB on the other Si after the break of the strained Si-Si bond, or (c) a Si-Si bond with bond length close to the equilibrium c-Si bond length (2.35 Å ) where the H atom is bonded to only one Si atom after the relaxation of the strained Si-Si bond. 10,39 Silicon hydrides in a platelet-like configuration in which the Si-H bonds are present along a planar defect, i.e., the grain boundaries, are formed just after the passivation of DBs in condition (b) mentioned above by H diffusion. Such a platelet-like configuration is similar to the structures observed in c-Si where Si-H bonds are predominantly oriented along {111} crystallographic planes.…”
Section: Resultsmentioning
confidence: 99%
“…5 It is generally believed that the optical and electrical properties of nc-Si:H thin films are strongly affected by the bonding configuration of hydrogen as well as its content in the films. 6 Bonded hydrogen in nc-Si:H thin films has been systematically investigated in several studies, [7][8][9][10] and the hydrides with stretching mode at around 2033 cm À1 are indentified as hydrides in a platelet-like configuration at grain boundaries resulting from the reaction of H-induced crystallization of a-Si:H during film deposition. 9,10 However, the role of these hydrides within nc-Si:H thin films remains to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen induced platelet formation in crystalline silicon (c-Si) has been reported earlier, 31 along with its theoretical investigations for different structural models. 38,39 At elevated pressures, the insertion of H into the network takes place at a higher intensity of the mono-hydride mode accompanied by its platelet-like conguration, as observed in Fig. It was earlier reported that the peak arises due to the formation of a hydrogen-dense compact grain boundary structure with good passivation in nc-Si:H thin lms.…”
Section: Discussionmentioning
confidence: 79%
“…These results are well consistent with the results of Raman and XRD measurements. Mobility and resistivity are showing opposite relationships to each other having the minimum mobility of ~37.5 cm 2 /v.s and the maximum resistivity of ~7.35 Ω-cm at 250 o C respectively (Vallat-Sauvain, Shah, & Bailat, 2006;Jana, Das, & Barua, 2002;Kamiya et al, 1999;Stieler et al, 2006;Agarwal et al, 2004;Das, 1995).…”
Section: Evaluation Of Surface Morphology Based On Sem Measurementsmentioning
confidence: 97%